Evaluating Properties and Applications of Innovative Recycled Aggregate Concrete - Kameshwar Sahani; Anish Kunwar; Prajwal Dhakal; Arjun Kunwar; Suresh Kumar Sahani; Binay Kumar Pandey; Digvijay Pandey (Engineering Reports)
ABSTRACT The global demand for concrete, driven by rapid industrialization and urbanization, has led to significant depletion of natural aggregates and increased environmental concerns. Natural aggregates, which constitute about 70%–80% of concrete mix volume, are essential for concrete production, but their extraction, processing, and transport contribute to considerable environmental degradation. The extensive demolition of old infrastructure due to urban growth generates massive construction and demolition waste (CDW), exacerbating landfill shortages and leading to contamination of groundwater and ecosystems. This paper explores the use of recycled aggregate concrete (RAC) derived from CDW as an alternative to natural aggregates, offering a sustainable solution to reduce waste, conserve natural resources, and minimize environmental impact. It examines the structural and environmental implications of RCA in concrete, particularly focusing on challenges such as high porosity, elevated water absorption, and reduced mechanical and durability performance. Strategies to overcome these limitations, such as incorporating supplementary cementitious materials (fly ash, silica fume), advanced mixing techniques like the Two‐Stage Mixing Approach (TSMA), and fiber reinforcement, are critically discussed. The review also emphasizes the role of numerical models and machine learning in optimizing RAC mix designs and predicting its behavior, offering valuable insights for sustainable construction practices. Furthermore, the study incorporates Life Cycle Assessment (LCA) to quantify environmental benefits and assesses real‐world applications and current codal provisions. The conclusions drawn suggest that RAC, if optimized with appropriate mix designs and processing methods, can significantly contribute to sustainable construction. However, more research is needed to standardize RCA processing methods and conduct long‐term field validations to further enhance its mechanical and durability properties. RAC not only presents an environmentally beneficial alternative to traditional concrete, but also supports a circular economy by reducing CDW and minimizing reliance on natural resources.